DESKRIPSI PROFIL PSYCHOLOGICAL OWNERSHIP DAN ORGANIZATIONAL COMMITMENT (Studi Lintas Generasi pada Karyawan Jawa Pos Group) - Intan Carissa Kirana; Mohammad Iqbal (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
The purpose of this research is to describe the characteristics of Psychological Ownership and Organizational Commitment of Generation X and Generation Y on Jawa Pos Group employees. The characteristics of the Psychological Ownership and Organizational Commitment of employees are an important factor in an organization. The type of research used in this study is descriptive research using a quantitative approach. The focus of this research is divided into two parts, namely, the first focus on the characteristics of the Psychological Ownership of the Jawa Pos Group employees. The second focus on the Organizational Commitment characteristics of the Jawa Pos Group employees. The data collected by researchers, derived from primary data and secondary data. From the results of research that has been done to get results that employees Jawa Pos Group has enough characteristics of Psychological Ownership and Organizational Commitment in the context of the organization. The Jawa Pos Group still needs to improve the characteristics of the Psychological Ownership and Organizational Commitment, and it is necessary to consider the auditor's recommendations for follow-up so that the characteristics of the future Psychological Ownership and Organizational Commitment of future employees can be improved. Kayword: Psychological Ownership, Organizational Commitment ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan karakteristik Psychological Ownership dan Organizational Commitment generasi X dan generasi Y pada karyawan Jawa Pos Group. Karakteristik Psychological Ownership dan Organizational Commitment pada karyawan merupakan faktor penting dalam sebuah organisasi. Jenis penelitian yang digunakan pada penelitian ini adalah descriptive research dengan menggunakan pendekatan kuantitatif. Fokus pada penelitian ini dibagi menjadi dua bagian yaitu, fokus yang pertama mengenai karakteristik Psychological Ownership pada karyawan Jawa Pos Group. Fokus kedua mengenai karakteristik Organizational Commitment pada karyawan Jawa Pos Group. Pengumpulan data yang dilakukan peneliti, berasal dari data primer dan data sekunder. Dari hasil penelitian yang telah dilakukan mendapatkan hasil bahwa karyawan Jawa Pos Group telah cukup memiliki karakteristik Psychological Ownership dan Organizational Commitment dalam konteks organisasi. Pihak Jawa Pos Group masih perlu untuk meningkatkan karakteristik Psychological Ownership dan Organizational Commitment, serta perlu untuk memperhatikan rekomendasi auditor untuk ditindaklanjuti agar karakteristik Psychological Ownership dan Organizational Commitment karyawan yang akan datang dapat ditingkatkan lagi. Kata Kunci: Psychological Ownership, Organizational Commitment